Regulation of Food Quality Development and Supervision in Denpasar City - Putri Febyana Br Surbakti (Susbtantive Justice International Journal of Law, 2019)
Guidance and supervision of food quality needs to be carried out in each region because of it given the high victims of food poisoning in Indonesia. The absence of regulations governing food hygiene and safety and the lack of public awareness are the reasons for the high incidence of food poisoning. Therefore it requires a firm attitude from the central and regional governments and socialization for the community regarding the importance of food hygiene and safety. This research aims to analyze the regulation of supervision and supervision of food quality in Denpasar City and the form of supervision and coordination between related agencies in sanitation hygiene and food safety supervision in Denpasar City. This research is normative legal research. This research can be summarized as follows: First, there is no explicit arrangement regarding the development and supervision of food quality in Denpasar City, but implicitly contained in the Regional Regulations of Denpasar City Number 7 of 2008 concerning the Organization and Work Procedures of Denpasar City and the Regulation of Mayor of Denpasar Number 33 of 2008 concerning the Description of Job Duties in the Denpasar Municipal Service Organization; and Twice, and Twice, The Government of Denpasar City through the Health Office in collaboration with BBPOM routinely conducts checks and supervisions of sanitation and security of processed food which is marketed in various regions in Denpasar City.